2018
DOI: 10.4236/wjet.2018.62028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ability of Two Different Pneumatic Boxing Gloves to Reduce Delivered Impact Forces and Improve Safety

Abstract: Two prototype pneumatic boxing gloves of different design were compared against conventional 10 oz (Std 10 oz) and 16 oz (Std 16 oz) gloves in terms of ability to reduce impact forces delivered to a target. One of the pneumatic gloves (SBLI) contained a sealed air bladder inflated to a pressure of 2 kPa. The other (ARLI) incorporated a bladder that allowed release of air to the external environment upon contact with a target, followed by rapid air reuptake. Each glove was placed on to a mechanical fist and dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Research in which force transducers were located in the gloves of professional boxers demonstrated that while most impacts recorded during actual bouts produced peak forces of less than 2000 N readings above 5000 N could be encountered [62]. Based on these findings and allowance of some tolerance to cater for the possibility that forces exceeding those observed in research settings might occasionally occur in field environ-Open Journal of Safety Science and Technology ments, gloves aimed at damping peak impact forces probably need to be effective across a range of standard glove equivalent peak forces extending from below 2000 N to at least 10,000 N. Our current ARLI gloves meet this criterion and, when employed in conjunction with other safety measures, could be expected to reduce the risk and/or severity of boxing injuries [57].…”
Section: Reflectionmentioning
confidence: 88%
See 2 more Smart Citations
“…Research in which force transducers were located in the gloves of professional boxers demonstrated that while most impacts recorded during actual bouts produced peak forces of less than 2000 N readings above 5000 N could be encountered [62]. Based on these findings and allowance of some tolerance to cater for the possibility that forces exceeding those observed in research settings might occasionally occur in field environ-Open Journal of Safety Science and Technology ments, gloves aimed at damping peak impact forces probably need to be effective across a range of standard glove equivalent peak forces extending from below 2000 N to at least 10,000 N. Our current ARLI gloves meet this criterion and, when employed in conjunction with other safety measures, could be expected to reduce the risk and/or severity of boxing injuries [57].…”
Section: Reflectionmentioning
confidence: 88%
“…In late April 2016, we conducted a study in which the drop testing apparatus was used to compare a Std 10oz glove, a Std 16oz glove, a prototype low-impact glove with a sealed bladder (SBLI), and the new prototype low-impact glove with air release capability (ARLI). This experiment is described in detail elsewhere [57]. Briefly, each glove was dropped on to the force plate 10 times from each of nine different heights ranging from 1 to 5 metres.…”
Section: Comparison Of Gloves Through Drop Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The data capture protocol is fully described elsewhere [1]. Two prototype pneumatic gloves and two conventional gloves were tested.…”
Section: Methodsmentioning
confidence: 99%
“…In this photo they are practising their sport-specific skills with specially constructed impact-damping boxing gloves that were developed by members of the research team as a means of improving participant safety and enjoyment. The gloves have been shown to significantly reduce peak impact forces [31]. Permission to use this image with the associated wording was provided by the people depicted.…”
Section: Theme 4 the Training: It Was Safe Fun And Beneficialmentioning
confidence: 99%